The Impact of Social Media Advertising and Brand Awareness on Waqf Re-Interest Mediated by Waqif Satisfaction - Yuda Dharma Putra; Sri Astuti Pratminingsih (UPT Publikasi Ilmiah UNISBA, 2025)
This study aims to analyze the effect of social media advertising and brand awareness on waqf intentions at Sinergi Foundation, with waqf satisfaction as a mediating variable. This research uses a quantitative approach with descriptive and verification methods. Data were collected through observations, interviews, and questionnaires distributed to 100 waqifs in the Bandung City Region who have interacted with the Synergy Foundation. The sampling technique used was purposive sampling, and the research instrument used was a Likert-scale questionnaire. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The results showed that brand awareness has a significant effect on waqf satisfaction and intention to return to waqf. Social media advertising has a significant effect on waqf satisfaction but does not directly affect re-engagement, the impact occurs indirectly through satisfaction. The findings emphasize the important role of donor satisfaction in driving repeat waqf participation. This study contributes to the development of digital marketing strategies that prioritize donor engagement and satisfaction to increase waqf loyalty.